1988
DOI: 10.1002/1097-0142(19880201)61:3<478::aid-cncr2820610312>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to 1,2-dimethylhydrazine-induced colonic tumors and epithelial cell proliferation characteristics of F1, F2, and reciprocal backcrosses derived from SWR/J and AKR/J parental mouse strains

Abstract: Hybrid crosses were performed between SWR/J, a strain highly sensitive to 1,2-dimethylhydrazine (DMH), and AKR/J, a strain highly resistant to the carcinogen. F1 and F2 and reciprocal backcrosses were tested to determine if proliferative characteristics such as high activity, wide compartment (PC), and a large S-phase population in the middle third of crypts were linked to susceptibility and inherited as a dominant autosomal trait as was reported for DMH tumor response. A blend of resistant and sensitive tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…These tumors consist in adenomas and in situ carcinomas, and a proportion of AOM-induced colon tumors have been shown to carry loss-of-function mutations in Apc and K-ras (Suzui et al, 2002;Takahashi and Wakabayashi, 2004; data not shown), highlighting the relevance of this model in the study of human tumors. Inbred strains of mice differ drastically in susceptibility to DMH or AOM chemical carcinogenesis (Evans et al, 1977;Deschner et al, 1988;Papanikolaou et al, 1998;Nambiar et al, 2003). In this study, we carried out a systematic analysis of the genetic control of differential response to AOM chemical carcinogenesis in A/J and C57BL/6J mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tumors consist in adenomas and in situ carcinomas, and a proportion of AOM-induced colon tumors have been shown to carry loss-of-function mutations in Apc and K-ras (Suzui et al, 2002;Takahashi and Wakabayashi, 2004; data not shown), highlighting the relevance of this model in the study of human tumors. Inbred strains of mice differ drastically in susceptibility to DMH or AOM chemical carcinogenesis (Evans et al, 1977;Deschner et al, 1988;Papanikolaou et al, 1998;Nambiar et al, 2003). In this study, we carried out a systematic analysis of the genetic control of differential response to AOM chemical carcinogenesis in A/J and C57BL/6J mice.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal tumors induced by these carcinogens harbor genetic lesions similar to those found in human CRCs, including mutations in Apc, K-ras and b-catenin (Takahashi and Wakabayashi, 2004). Inbred mouse strains vary dramatically in susceptibility to carcinogeninduced CRC, as determined by the number of tumors (>1 mm diameter) arising over time: strains such as A/J, FVB/J, ICR/Ha, SWR and STS/A being susceptible and strains such as C57BL/6, BALB/c, AKR and DBA/ 2J being resistant to DMH and/or AOM-induced CRC (Evans et al, 1977;Deschner et al, 1988;Papanikolaou et al, 1998;Nambiar et al, 2003). In F1 hybrids, susceptibility tends to be co-dominant, and segregation analyses and whole-genome scanning have pointed to loci on chromosomes 3 (CBA  C57BL/6 cross) (Angel et al, 2000), 4 (B10.O20  O20 cross) (Fijneman and Demant, 1995) and 12 (ICR/Ha  C57BL/6Ha cross) (Jacoby et al, 1994), as contributing in a strain-specific manner to susceptibility to DMH-induced CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Strain sensitivity in mice As in human populations, genetic background of laboratory animals is a significant component of organ-specific carcinogenesis. Genetically defined inbred mouse strains that differ in their sensitivity to colon carcinogens offer distinct advantages for studying organ-specific carcinogenesis (Table I been shown to be relatively resistant to colon tumor development, whereas Balb/cHea and SWR/J are moderately sensitive and A/J, P/J, STS/A and ICR/Ha are highly sensitive to DMH (21,(38)(39)(40)(41)(42)(43)(44). These reported differences, however, are often variable and probably the result of environmental conditions under which the animals are maintained.…”
Section: Genetic Background Modulates Carcinogen-induced Tumors In Rodentsmentioning
confidence: 99%
“…These include rates of carcinogen activation/detoxification, the extent of acute DNA alkylation and the efficiency of repair (16). In addition, the balance between proliferation and apoptosis of initiated colon crypt cells has also been examined (39,47). Based on proliferation kinetics, it was suggested that AKR expresses a protective or resistance factor (repressor gene) that impedes progression of carcinogen-induced foci into colon tumors (39).…”
Section: Genetic Background Modulates Carcinogen-induced Tumors In Rodentsmentioning
confidence: 99%
“…Another factor which may play a role in differences in somatic stem cell mutation frequency among strains may be differences in the proliferative activity of stem cells. Differences which have been documented among strains with respect to the labelling index, size of the proliferative compartment, and the distribution of proliferative cells have a positive correlation with susceptibility to DMH‐induced carcinogenesis25–27. Balb/C mice have been shown to have significantly larger colonic crypts than C57BL/6J mice28; this may correlate with increased stem cell proliferative activity.…”
Section: Discussionmentioning
confidence: 98%